THE IMPACT OF WORLD OIL PRICE FLUCTUATIONS AND EXCHANGE RATES ON THE CURRENT ACCOUNT BALANCE IN INDONESIA - Hardi, Bima; Widya, Heni; Ramzani, Ikbal (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The position of the Current Account Balance is very important to maintain, because for a country the current account balance describes the situation or state of the economy in a country so it is important to pay attention to its development . This study was conducted to determine the impact of fluctuations in world oil prices and the rupiah exchange rate simultaneously and partially on the current account balance in Indonesia. This study is a quantitative study using the Ordinary Least Square (OLS) method. The results of the study indicate that simultaneously fluctuations in world oil prices and the rupiah exchange rate have a significant effect on the current account balance. Partially, the world oil price variable has an effect on the current account balance. Partially, the rupiah exchange rate variable has an effect on the current account balance. The current account balance variable can be explained by the world oil price variable and the rupiah exchange rate by 47.72% and the remaining 52.28% is explained by other variables that are not included in the equation model of this study.